2002
DOI: 10.1210/jcem.87.3.8316
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Growth Differentiation Factor-9 in Oocytes of Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a major cause of female infertility. Despite substantial effort, the etiology and pathogenesis of PCOS and polycystic ovaries (PCO) in women remain unknown. Recent studies in laboratory animals have documented a link between dysfunction of two oocyte growth factors, growth differentiation factor-9 (GDF-9) and bone morphogenetic factor-15 (BMP-15), and aberrant folliculogenesis. Because aberrant follicle development is a hallmark of PCOS, we wondered whether the expression pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(46 citation statements)
references
References 49 publications
1
44
1
Order By: Relevance
“…Interleukin-6 is on 7p21 chromosome. International Journal of Cellular & Molecular Biotechnology 2014 (2014 [1][2][3][4][5][6][7][8][9][10][11][12] Available online at www.ispacs.com/ijcmb is basically regulated by Beta Kappa core factor (NK-kb) and interleukin IL-6 causes stimulus, regulates synthesis of acute phase protein, activates axis of hypothalamus -pituitary and disorder in signal transduction of glucose through changing activity of serine -threonine kinases. Interleukin-6 plays a key role in the pathogenesis of chronic inflammation, insulin resistance, and CV diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 is on 7p21 chromosome. International Journal of Cellular & Molecular Biotechnology 2014 (2014 [1][2][3][4][5][6][7][8][9][10][11][12] Available online at www.ispacs.com/ijcmb is basically regulated by Beta Kappa core factor (NK-kb) and interleukin IL-6 causes stimulus, regulates synthesis of acute phase protein, activates axis of hypothalamus -pituitary and disorder in signal transduction of glucose through changing activity of serine -threonine kinases. Interleukin-6 plays a key role in the pathogenesis of chronic inflammation, insulin resistance, and CV diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in these genes lead to reproductive defects in animals and with the recombinant forms of these growth factors the actions of the oocyte can be mimicked (Gilchrist et al 2004b). Further, mutations in the human BMP15 or GDF9 genes are associated with polycystic ovary syndrome Page 2 of 27 A c c e p t e d M a n u s c r i p t 2 (PCOS), premature ovarian failure (POF) or dizygotic twinning (Teixeira Filho et al 2002;Di Pasquale et al 2004;Dixit et al 2005;Di Pasquale et al 2006;Dixit et al 2006;Laissue et al 2006;Palmer et al 2006). Furthermore, both proteins have been shown to regulate ovulation rate in sheep (Galloway et al 2000;Juengel et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the hGDF9 gene are associated with various reproductive abnormalities. It has been shown that aberrant expression of GDF9 is associated with polycystic ovary syndrome (PCOS) (Teixeira Filho et al 2002) and screening of women with premature ovarian failure (POF) has revealed mutations in the GDF9 gene (Dixit et al 2005;Laissue et al 2006). In 2004 a rare deletion mutation in the hGDF9 gene was described in heterozygous sisters with spontaneous dizygotic twins (Montgomery et al 2004) and more recently new variants in the hGDF9 gene that are significantly more common in mothers of dizygotic (DZ) twins than controls were described, suggesting that rare GDF9 variants contribute to the likelihood of DZ twinning (Palmer et al 2006).…”
Section: Introductionmentioning
confidence: 99%